2019
DOI: 10.4049/jimmunol.1801420
|View full text |Cite
|
Sign up to set email alerts
|

EBV Latency III–Transformed B Cells Are Inducers of Conventional and Unconventional Regulatory T Cells in a PD-L1–Dependent Manner

Abstract: EBV infects and immortalizes B cells in vitro and in vivo. It is the causative agent of most immune deficiency–related lymphoproliferative disorders and is associated with various lymphomas. EBV latency III–transformed B cells are known to express two immunosuppressive molecules, IL-10 and PD-L1, two characteristics of regulatory B cells (Bregs). In this study, we show that, in addition to secretion of the Breg immunosuppressive cytokines IL-10, IL-35, and TGF-β1, EBV latency III–transformed B cells were able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
13
1
Order By: Relevance
“…Of note, the correlation between LAG-3 and PD-1 observed in EBV-associated pediatric cHL, not proved on the non-associated cases, supports the notion of viral infection to promote exhaustion. Even though an increased LAG-3 expression was demonstrated previously in EBV-associated adult cHL, related to the loss of viral LMP-1 specific T-cell function (16), it was not proved in relation to PD-1 expression as observed in our series.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Of note, the correlation between LAG-3 and PD-1 observed in EBV-associated pediatric cHL, not proved on the non-associated cases, supports the notion of viral infection to promote exhaustion. Even though an increased LAG-3 expression was demonstrated previously in EBV-associated adult cHL, related to the loss of viral LMP-1 specific T-cell function (16), it was not proved in relation to PD-1 expression as observed in our series.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, LAG-3 acts synergistically with PD-1 and/or CTLA-4 to negatively regulate T-cell expansion (15). EBV latency III-transformed B cells exhibit strong immunoregulatory properties since they induce regulatory T cells that express PD-1 (16). In EBVassociated adult and pediatric cHL, PD-1 expression was not related to viral presence (17), whereas LAG-3 expression remains unexplored so far.…”
Section: Introductionmentioning
confidence: 99%
“…The immune regulatory environment observed in EBV + DLBCL also involves increased gene expression of immunosuppressive cytokine IL10 [ 68 ], which could be triggered directly by LMP1 [ 93 ], and/or lytic antigens [ 55 ], or, alternatively, by the presence of regulatory T cells that secrete IL10, as observed in EBV-associated HL, nasopharyngeal and gastric carcinomas, and in EBV-transformed B cell lines [ 84 , 94 ]. However, in EBV + DLBCL the regulatory environment coexists with the increased expression of CD8+ T-cells and granzyme B+ cytotoxic effector cells [ 68 ], also known as “inflamed phenotype” by gene expression analysis [ 72 ].…”
Section: Microenvironment Compositionmentioning
confidence: 99%
“…Although we have not yet identified an EBV-specific molecular and immunologic mechanism by which PD-1 blockade may have affected the CD4 + Tregs function, some correlations exist with neoplasias caused by EBV. For example, in vitro studies showed that EBV latency III–transformed B cells promoted expansion of autologous FoxP3 + CD39 high PD-1 + CTLA-4 + Helios + GITR + LAG-3 + CD4 Tregs ( 53 ). Another study showed that homing of Tregs in EBV + HL tumor microenvironment is significantly increased around EBV-infected cell nests ( 54 ).…”
Section: Discussionmentioning
confidence: 99%